2001
DOI: 10.1159/000052776
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Constipation in the Elderly Improves Lower Urinary Tract Symptoms

Abstract: Background: Constipation and lower urinary tract symptoms (LUTS) very frequently occur in the elderly, and several reports have suggested that dysfunction in either one of these systems may affect the other. Most studies correlating rectal and bladder dysfunction, however, have been carried out in children or young women. Objective: To examine the effect of alleviating constipation on LUTS in the elderly. Methods: Fifty-two patients aged 65–89 (mean 72 ± 13) years with chronic constipation and LUTS participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 14 publications
(22 reference statements)
3
42
1
4
Order By: Relevance
“…However, the inhibition of urinary bladder micturition in some animals was released following the deflation of the distal colon balloon. Similar effects were also reported in the elderly people, where treating constipation in these patients had improved the urinary bladder dysfunction and decreased the bladder residual volume [3]. The results of this study also showed that voiding time, but not the storage time, had significantly increased with colon distention.…”
Section: Discussionsupporting
confidence: 85%
“…However, the inhibition of urinary bladder micturition in some animals was released following the deflation of the distal colon balloon. Similar effects were also reported in the elderly people, where treating constipation in these patients had improved the urinary bladder dysfunction and decreased the bladder residual volume [3]. The results of this study also showed that voiding time, but not the storage time, had significantly increased with colon distention.…”
Section: Discussionsupporting
confidence: 85%
“…7,8 Research in the elderly population has shown that LUTS improve after the relief of constipation. 9 In this study we examine the association of LUTS with abnormalities in bowel habits among men age 40 years or older using a large database representative of the United States population. We hypothesize that men with LUTS have concomitant abnormalities in bowel habits.…”
mentioning
confidence: 99%
“…9 In a cohort of women age 65 to 89 years with lower urinary tract symptoms and constipation, treatment of constipation resulted in decreased rates of urinary frequency and urgency and reduced postvoid residual urine volume. 10 …”
Section: Acute Incontinencementioning
confidence: 99%